Identification of Associations between Bacterioplankton and Photosynthetic Picoeukaryotes in Coastal Waters - Farnelid, Hanna M.; Turk-Kubo, Kendra A.; Zehr, Jonathan P. (Frontiers in Microbiology, 2016)
Photosynthetic picoeukaryotes are significant contributors to marine primary productivity. Associations between marine bacterioplankton and picoeukaryotes frequently occur and can have large biogeochemical impacts. We used flow cytometry to sort cells from seawater to identify non-eukaryotic phylotypes that are associated with photosynthetic picoeukaryotes. Samples were collected at the Santa Cruz wharf on Monterey Bay, California during summer and fall, 2014. The phylogeny of associated microbes was assessed through 16S rRNA gene amplicon clone and Illumina MiSeq libraries. The most frequently detected bacterioplankton phyla within the photosynthetic picoeukaryote sorts were Proteobacteria (Alphaproteobacteria and Gammaproteobacteria) and Bacteroidetes. Intriguingly, the presence of free-living bacterial genera in the photosynthetic picoeukaryote sorts could suggest that some of the photosynthetic picoeukaryotes were mixotrophs. However, the occurrence of bacterial sequences, which were not prevalent in the corresponding bulk seawater samples, indicates that there was also a selection for specific OTUs in association with photosynthetic picoeukaryotes suggesting specific functional associations. The results show that diverse bacterial phylotypes are found in association with photosynthetic picoeukaryotes. Taxonomic identification of these associations is a prerequisite for further characterizing and to elucidate their metabolic pathways and ecological functions.